Assessment of Physicochemical Parameters and Contaminants in Herbal Dietary Supplements Used in the Treatment of Inflammatory Bowel Disease - Daniela Amidžić Klarić; Jelena Kovačić; Mario-Livio Jeličić; Snježana Zubčić; Vladimir Stankov; Marija Gulan Čičak; Boris Bučar; Ilija Klarić; Ana Mornar (MDPI AG, 2023)
Inflammatory bowel disease is a complex disorder characterized by chronic gastrointestinal inflammation. Thus, patients prefer to use herbal dietary supplements containing turmeric, Indian frankincense, green chiretta, and black pepper in an attempt to cope better with their chronic condition. The dietary supplements' dosage forms and herbal ingredients were assessed in terms of the products' physicochemical parameters (weight uniformity, friability, disintegration, rupture test, tablet's breaking force, and powder flowability) in view of the USP-NF requirements. In addition, contaminants such as organic solvents and ethylene oxide were evaluated using gas chromatography. Assessment of gluten via an Enzyme-Linked Immunosorbent Assay was also performed. Most of the products met USP requirements. The high average weight of one multicomponent tablet sample with a high breaking force value can explain the observed negative results of the disintegration test. A total of 26% of samples tested positive for gluten, but the most alarming fact is that the ethylene oxide levels found in two samples were up to 30 times higher than the EU limit. Accordingly, dietary supplement quality control is of fundamental importance.